Chronic Variable Stress May Induce Apoptosis in the Testis and Epididymal Sperm of Young Male Rats - Yeimy Mar De León-Ramírez; Leticia Nicolás-Toledo; Eliut Pérez-Sánchez; Omar Arroyo-Helguera (Biology, 2025)
Stressor stimuli induce oxidative stress and functional abnormalities in sperm, which are linked to a reduced sperm quality and male infertility. Furthermore, oxidative stress can trigger cell death. However, the impact of stressor stimulation on testicles and epididymal sperms and apoptosis has not been explored. This study analyzes the expression of extrinsic and intrinsic apoptotic markers in the testicle and epididymis of rats exposed to chronic variable stress (CVS). We used male Wistar rats divided into two groups: the control group was kept undisrupted, and the stress group was stressed daily using a CVS model for four weeks, except for the weekends (from postnatal days 51 to 81). After the last week, the rats were sacrificed, and complete testicles and epididymal sperm were used to measure oxidative stress and the total antioxidant status by colorimetric methods. The expressions of PPAR-γ, p53, Bax, and Bcl-2 markers at the mRNA level were determined by real-time PCR, and the p-Akt, AP-2α, PPAR-γ, C/EBP-β and FAS protein levels were detected by immunoblot. The results showed low levels of p-Akt and AP-2α proteins and high levels of FAS, PPAR-γ, and C/EBP-β in the testicle and epididymis of rats exposed to CVS. At the mRNA level, we observed the upregulation of PPAR-γ, p53, p21, HIF-α, and Bax expressions in the epididymis of rats exposed to CVS, consistent with the significant caspase-3 activity observed in both the epididymis and testicles in the CVS group. In conclusion, CVS damage triggers the induction of apoptosis markers by intrinsic (PPAR-γ, p53, p21, HIF-α, and Bax) and extrinsic (p-Akt, AP-2α, and FAS) caspase-3-dependent pathways in complete extracts of both the testicles and epididymis. This study supports the view that stressor stimuli could be involved in the infertility process.